THE EFFECTIVENESS OF COCOPEAT AS A PLANTING MEDIA ON THE GROWTH OF SOME OIL PALM VARIETIES (Elaeis guineensis Jacq) - Fenty Maimunah Simbolon; Noverina Chaniago; Abdul Hakim Hutasuhut (International Journal of Educational Research Excellence (IJERE), 2022)
The purpose of the study was to determine the growth of several oil palm to the application of cocopeat as a growing medium. This research was carried out at the Experimental Garden of the Faculty of Agriculture, Islamic University of North Sumatra, Medan, which is located on Jalan . Karya Wisata, Johor Building, Medan Johor District, Madya City, North Sumatra Province with an altitude of ± 25 m above sea level, air humidity (RH) 68% and flat topography. The research was carried out from January-March 2016. This research used a factorial randomized block design (RBD) with two factors, namely: Cocopeat as a planting media mixture consists of 4 levels: C0 = Topsoil (Control) , C1 = Topsoil: cocopeat not soaked (2: 1) , C2 = Topsoil: cocopeat soaked in a bucket (2: 1) , C3 = Topsoil: cocopeat soaked in running water (2: 1) . The use of several varieties of oil palm consists of 3 levels: V1 = Simalungun SP540 DXP , V2 = Yangambi DXP PPKS718 , V3 = Langkat DXP Langkat. The research results showed that the growth of several oil palm varieties had no significant effect on all treatment parameters. The use of cocopeat had a significant effect on the number of leaves, but had no significant effect on plant height, leaf area , leaf chlorophyll, base weight and dry weight. Good growth was seen when cocopeat was soaked in C3 running water. The interaction of cocopeat with several oil palm varieties had a significant effect on the number of leaves of oil palm seedlings, whereas it had no significant effect on the other treatments.